ANALISA KEPUASAN MAHASISWA TERHADAP JASA PENDIDIKAN DI UNIVERSITAS BATANGHARI - AS, Sakinah (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Heightened competition is going on between universities both domestically and abroad, in the end each of the universities compete to provide maximum service in accordance with the needs of its customers, the customer in question here are students, the University of Batanghari as service providers Education regard, it is necessary to think about student satisfaction, because the presence of satisfaction or dissatisfaction that occurs can be used as a benchmark on the success of the University of Batanghari in marketing education. Therefore, it is necessary to study how far the relationship between variables in meeting the needs of students, which in terms of education (teaching) and the Bureau of Academic Administration.Faculty who made the object of research is the Faculty of Economics, University of Batanghari in the Economic Studies Program Development and Management Program S1. Results showed variable master lecturer with good teaching material having a high mean value in the Faculty of Economics. There are differences in the variable lecturers present at every lecture schedule, and curriculum used in accordance with the needs of the world of work have mean values were higher in S1 Management Studies Program Faculty of Economics, University of Batanghari.Key Word: student satisfaction